1996
DOI: 10.1007/bf00196660
|View full text |Cite
|
Sign up to set email alerts
|

High-irradiance responses induced by far-red light in grass seedlings of the wild type or overexpressing phytochrome A

Abstract: Abstract. The occurrence of phytochrome-mediated highirradiance responses (HIR), previously characterised largely in dicotyledonous plants, was investigated in Triticum aestivum L., Zea mays L., Lolium muhiflorumLam. and in both wild-type Oryza sativa L. and in transgenic plants overexpressing oat phytochrome A under the control of a 35S promoter. Coleoptile growth was promoted (maize, ryegrass) or inhibited (wild-type rice) by continuous far-red light (FRc). However, at equal fluences, hourly pulses of far-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
22
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 36 publications
8
22
0
Order By: Relevance
“…We think that in the wild type, the FR pulse-induced reverse response mediated mainly by phyB was almost canceled by phyAmediated growth inhibition induced by the FR pulse. The results presented here clearly show that the coleoptile elongation in wild-type plants is inhibited by a FR light pulse and are consistent with the results using a single short exposure (Pjon and Furuya, 1967) or hourly pulses of FR light exposure (Casal et al, 1996). In addition, we have demonstrated that a pulse of VLF-R or FR light that inhibited the coleoptile elongation in wild-type seedlings was not effective for the inhibition of coleoptile elongation in phyA mutants (Figure 6, Seven-day-old etiolated seedlings of wild type (Nipponbare [N]) and two independent phyA mutants (osphyA-1and osphyA-2) were exposed to continuous R light (cR) or continuous FR light (cFR) for 0, 4, 12, and 24 hr (h) and harvested for RNA isolation.…”
Section: Role Of Phya In the Photomorphogenesis Of Rice Seedlingssupporting
confidence: 91%
“…We think that in the wild type, the FR pulse-induced reverse response mediated mainly by phyB was almost canceled by phyAmediated growth inhibition induced by the FR pulse. The results presented here clearly show that the coleoptile elongation in wild-type plants is inhibited by a FR light pulse and are consistent with the results using a single short exposure (Pjon and Furuya, 1967) or hourly pulses of FR light exposure (Casal et al, 1996). In addition, we have demonstrated that a pulse of VLF-R or FR light that inhibited the coleoptile elongation in wild-type seedlings was not effective for the inhibition of coleoptile elongation in phyA mutants (Figure 6, Seven-day-old etiolated seedlings of wild type (Nipponbare [N]) and two independent phyA mutants (osphyA-1and osphyA-2) were exposed to continuous R light (cR) or continuous FR light (cFR) for 0, 4, 12, and 24 hr (h) and harvested for RNA isolation.…”
Section: Role Of Phya In the Photomorphogenesis Of Rice Seedlingssupporting
confidence: 91%
“…For example, Arabidopsis mutants lacking PHYA produce elongated hypocotyls when grown under a canopy (Johnson et al, 1994;Yanovsky et al, 1995), whereas strong overexpression reduces internode elongation in several species. This is often attributed to PHYA inhibition of GA biosynthesis in vascular tissue (Boylan and Quail, 1991;Jordan et al, 1995;Casal et al, Cell division walls are anticlinal in the tunica (cell layers 1 and 2), random in the corpus (approximate cell layers 3 to 8), and periclinal in the RM (approximate cell layers 9 to 11) and upper RZ. PZ, peripheral zone; CZ, central zone; p 0 , youngest leaf primordium; T, tunica; C, corpus.…”
Section: Phya Abundance and Spatial Distribution Affect Stem Growthmentioning
confidence: 99%
“…At least in Arabidopsis, hypocotyl growth inhibition by FR is a HIR because it shows reciprocity failure (Mazzella et al 1997). Overexpression of oat phyA in transgenic tobacco (McCormac et al 1991), Arabidopsis (Whitelam et al 1992) and rice (Casal, Clough & Vierstra 1996), rice phyA in transgenic tobacco (Emmler et al 1995) and potato phyA in transgenic potato (Heyer et al 1995) enhances the response to continuous FR. Neither Arabidopsis nor rice phyB overexpressed in transgenic Arabidopsis appears to enhance HIR (McCormac era/.…”
Section: De-etiolation Under Dense Canopiesmentioning
confidence: 99%